2008
DOI: 10.2319/022507-96.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperbaric Oxygen during Experimental Tooth Movement

Abstract: Objective: To determine the effects of hyperbaric oxygen (HBO) on bone remodeling during orthodontic tooth movement. Materials and Methods: Twenty-four male, adult Sprague Dawley rats were randomly divided into two groups. HBO was administered in the first group, and the second group served as a control. The mandibular first molars were moved mesially by means of Ni-Ti closed coil springs in all groups. Results: Results were evaluated histomorphometrically and the parameters of trabecular bone volume (BV/TV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
0
14
0
9
Order By: Relevance
“…They also suggested that the hyperbaric oxygen enhanced the bone formation during experimental tooth movement. (22) This can be explained by HBO increases dissolved oxygen in the blood and results in a high partial pressure of oxygen (PaO 2 ). An increase of PaO 2 affects the oxygen tension in regenerating tissue, which promotes collagen and adenosine-triphosphate (ATP) synthesis, capillary growth, and osteoblastic and osteoclastic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that the hyperbaric oxygen enhanced the bone formation during experimental tooth movement. (22) This can be explained by HBO increases dissolved oxygen in the blood and results in a high partial pressure of oxygen (PaO 2 ). An increase of PaO 2 affects the oxygen tension in regenerating tissue, which promotes collagen and adenosine-triphosphate (ATP) synthesis, capillary growth, and osteoblastic and osteoclastic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation of the smaller degree of tipping in the hyperbaric group can be attributed to the role of hyperbaric oxygen in enhancing the bone formation during experimental tooth movement. (22) While the smaller degree of tipping in the dentoalveolar side compared to the periodontal ligament side might be attributed to the surgical technique of dentoalveolar distraction does not rely on periodontal stretching, which obviates overloading and stress accumulation in this tissue. (7) The use of the dentoalveolus itself in the dentoalveolar technique might have a role in reducing the degree of tipping allowing the bodily movement of the canine during distracion.…”
Section: Volume 44 -December 2013mentioning
confidence: 99%
“…Et cette stimulation des ostéoblastes s'accompagnerait, selon Gokce et al, d'une inhibition des ostéoclastes [61].…”
Section: Impact De L'ohb Sur La Cicatrisation Du Tissu Osseuxunclassified
“…Une semaine après la greffe, la néo-formation d'os était plus importante dans le groupe ayant été soumis à l'OHB. Selon Gocke et al, l'OHB affecte le taux de résorption osseuse soit par stimulation des ostéoblastes, soit par inhibition des ostéoclastes [40].…”
Section: Impact De L'ohb Sur La Survie Des Implants En Terrain Irradiéunclassified